Towards Developing a Screening Strategy for Ecstasy: Revealing the Electrochemical Profile. Issue 24 (22nd December 2021) - Thiruvottriyur Shanmugam, Saranya; Van Echelpoel, Robin; Boeye, Griet; Eliaerts, Joy; Samanipour, Mohammad; Ching, H. Y. Vincent; Florea, Anca; Van Doorslaer, Sabine; Van Durme, Filip; Samyn, Nele; Parrilla, Marc; De Wael, Karolien
Abstract: This article describes the development of an electrochemical screening strategy for 3, 4‐methylenedioxymethamphetamine (MDMA), the regular psychoactive compound in ecstasy (XTC) pills. We have investigated the specific electrochemical profile of MDMA and its electro‐oxidation mechanisms at disposable graphite screen‐printed electrodes. We have proved that the formation of a radical cation and subsequent reactions are indeed responsible for the electrode surface passivation, as evidenced by using electron paramagnetic resonance spectroscopy and electrochemistry. Thereafter, pure cutting agents and MDMA as well as simulated binary mixtures of compounds with MDMA were subjected to square wave voltammetry at pH 7 to understand the characteristic electrochemical profile. An additional measurement at pH 12 was able to resolve false positives and negatives occurring at pH 7. Finally, validation of the screening strategy was done by measuring a set of ecstasy street samples. Overall, our proposed electrochemical screening strategy has been demonstrated for the rapid, sensitive, and selective detection of MDMA, resolving most of the false positives and negatives given by the traditional Marquis color tests, thus exhibiting remarkable promises for the on‐site screening of MDMA. Abstract : Ecstasy screening : Understanding the electrochemical oxidation mechanism of methylenedioxymethamphetamine (MDMA) and developing a screening strategy for street samples led to electrochemical profiling of MDMA.